PENGARUH ELEMEN CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This research aims to investigate the CSR (Corporate Social Responsibility)disclosure practice of banks located in Indonesia and explores the effects ofCorporate Governance (CG) structure elements on bank CSR voluntary disclosures.The investigated elements of Corporate Governance structure are Board ofCommissioner Independency, Audit Comittee Independency, InstitutionalOwnership, and Managerial Ownership. The population of this research is 31general banks which are listed in Indonesia Stock Exchange (BEI) in the period2009-2011. By purposive sampling, the collected sample is 28 banks while the datasource is the annual reports in number 84 reports. Data analysis used is contentanalysis, processed in test of classic assumption while the hypothesis analysismethod was done with the multiple linear regression method. Result of this researchindicates that Board of Commissioner Independency, Audit CommitteeIndependency, Institutional Ownership, and Managerial Ownership had aninfluencing significant negative with adjutsted R2 0.234. This suggests that there areother factors that can affect the Corporate Social Responsibility Disclosure.Keywords: Corporate social responsibility, corporate governance, board ofcommissioner independency, audit comittee independency, institutionalownership, and managerial ownership.